The Perspectives of Males with Serious Mental Disorders on their Community Integration following a Residential-based Rehabilitation Programme in South Africa: "It's a catch-22 situation". - Gamaldien, Fadia; Galvaan, Roshan; Duncan, Madeleinde (South African Journal of Occupational Therapy, 2021)
Introduction: Residential-based rehabilitation programmes were introduced by the Western Cape Department of Health in 2008 to relieve the burden of long-term hospitalization in South Africa. In South Africa, more men than women of working age require long-term support from public mental health services. Most of these healthcare users live in communities characterised by poverty and unemployment. There is limited research on male mental health service users' perspectives on the impact that residential-based rehabilitation programmes have on their community integration. The aim of the study was to inform the continuum of care for people with serious mental disorders to better align residential-based rehabilitation and primary care public mental health services with the recovery needs of mental health service users. Method: An instrumental case study design was applied, and five male participants were identified through purposive sampling. Observations, semi-structured interviews, community maps and document analysis were used to collect data. Thematic cross-case analysis of qualitative data was done. Findings: The theme, It's a catch-22 situation, describes the participants' ambivalence towards the residential-based rehabilitation programme's contribution to their community reintegration after discharge. Three categories, namely 'It's not just what you call it', 'There's no one size for all', and 'It's tricky choosing between places to go and things to do', capture how the perceived inflexibility of the programme curtailed their adjustment to community living. Conclusion: Participants proposed co-constructing their recovery plan with mental health professionals so that it is more personalised in supporting them as they adapt to emergent occupational challenges. It is recommended that a seamless continuum of support between different levels of care should be implemented.